Optimal 2-DOF PID controller design for load frequency control with various nonlinearities - Jena, Tarakanta; Kumar Debnath, Manoj; Prasad Ray, Prateek; Kumar Sanyal, Smaran (International Journal of Engineering and Technology, 2018)
This article includes an efficient and effective hybrid optimization technique called as Differential Evolution - Particle Swarm Optimization (DE-PSO) is used to optimize the controller gains parameters of two-degree of freedom-proportional-integral-derivative controller (2-DOF-PID) by considering the Integral time absolute error (ITAE) in load frequency control of three area non-linear interconnected reheat thermal system. The nonlinearities of the system are implemented by generation rate constraints (GRC) in each of the control areas. The incompara-bility of the suggested method is recognized above some pre-published outputs. The domination of 2-DOF-PID controller in conditions of responses of the settling time, minimum undershoots & overshoot over other controllers is proved on the nonlinear system. For the verifica-tion of the robustness of the mentioned controller a time delay is introduced in the scrutinized system as a second source of nonlinearity.Â Â